TEST-BASED CONTROL AS A MEANS OF DIAGNOSING THE ACADEMIC ACHIEVEMENTS OF STUDENTS MAJORING IN SPECIAL EDUCATION: A CASE STUDY OF THE CURRICULUM EDUCATIONAL COMPONENT «GENERAL PEDAGOGY WITH HISTORY» - Сергеєва, Валентина (SWorldJournal, 2024)
The article highlights the issue of using tests as a diagnostic and verification of the academic achievements of students. The educational process in the institution of higher education is carried out following the principles of the Bologna system of educ